MST e a criação do FINAPOP:a experiência da cooperativa COOPAN do assentamento Capela/RS - Bruch, Christian Alan (2023)
This dissertation is an analysis of the creation of “Popular Financing” (FINAPOP) by the Landless Rural Workers Movement (MST) and its first resource mobilization through Agribusiness Receivables Certificates (CRA) in the Capital Market by the Agricultural Production Cooperative Nova Santa Rita LTDA (COOPAN) of the Capela Settlement located in Nova Santa Rita/RS. The main objective of this research is to understand the paths that led MST to create FINAPOP and the vision and perspectives surrounding its creation. Additionally, it aims to analyze, based on COOPAN, the first agrarian reform cooperative to conduct resource mobilization, how it developed, and the possible impacts on the work, income, production, and quality of life of the cooperative members. For the realization of this research, a bibliographic review was conducted based on studies from books, magazines, and summaries. Additionally, a questionnaire was administered to 15 COOPAN members, and scripted interviews were conducted with two settlers from the cooperative, one from MST, and another person from the Gaia group. The application of questionnaires and conducting of interviews served as the primary sources for this work. The structure is divided into three chapters: In the first chapter, I present a discussion of peasant struggles in Brazil, covering various historical periods: from the colonial era to the republic. It explores the different forms of violations against the rural population and their process of resistance through revolts, conflicts, and strikes. It also examines how they organized themselves into movements, associations, and unions while fighting for their rights. Additionally, the second chapter aims to highlight how the process of land appropriation occurred in Rio Grande do Sul and the emergence and consolidation of social movements in rural areas fighting for land rights. It delves into the history of the Movement of Landless Farmers (MASTER) before 1964 and the subsequent formation and growth of the Landless Rural Workers Movement (MST) after the 1980s. Furthermore, it examines the process of struggle and land acquisition in the Capela settlement. The third chapter seeks to understand the reasons that led MST to create FINAPOP, by examining the perspectives of the settlers regarding FINAPOP. This analysis aims to comprehend the context of the land struggle within which the creation of this program took place. Additionally, the chapter aims to understand the paths that led COOPAN to become the first cooperative to mobilize resources in the Capital Market. Furthermore, it explores the impacts of this resource mobilization on the relationships of work, income, production, and the quality of life of the cooperative members.